Crystal structure of tetracene-5,12-dione, C18H10O2 - Zheng Xiaoxin; Jiang Jinke; Liu Yang (Zeitschrift für Kristallographie - New Crystal Structures)
C18H10O2, orthorhombic, P212121 (no. 19), a = 3.95660(10) Å, b = 12.2859(3) Å, c = 24.5014(6) Å, V = 1191.02(5) Å3, Z = 4, Rgt ${R}_{gt}$ (F) = 0.0609, wRref $wR_{ref}$ (F 2) = 0.1660, T = 302(2) K.